The Effect of Religiosity and Emotional Intelligence on the Performance of the Management of the Student Organization with Motivation as Intervening Variable - Zulhazzi Siregar; Sugianto Sugianto; Marliyah Marliyah (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2021)
Islamic Boarding School is a life-oriented Islamic education institution that emphasizes the importance of having a religious attitude and good emotional intelligence in students as a form of motivation that supports good performance and brings the good name of the Islamic boarding school. This study aims to prove how the direct and indirect influence of Religiosity and Emotional Intelligence on performance with motivation as an intervening variable. The sample in this study was the member of the Student Organization of Modern Islamic Boarding School Nurul Hakim Tembung, totaling 47 people. The method used in this research is a quantitative approach using path analysis with multiple linear regression models with SPSS version 20. The results of this study found that religiosity does not affect motivation. Emotional intelligence has a significant effect on motivation. Motivation does not affect performance. Indirectly Religiosity does not affect performance through motivation. Emotional intelligence indirectly does not affect performance through motivation. Religiosity, Emotional Intelligence, Motivation, Performance.